Perspectives on Aging and End of Life Among Lower Socioeconomic Status (SES) Older Adults. (June 2022) - Coogan, Anne; Kimpel, Christine; Jones, Abigail C.; Barroso, Julie; Frechman, Erica; Maxwell, Cathy A.
Objective: To explore the experiences of aging that influence perceptions of and receptivity to planning for aging and EOL among lower SES older adults.Methods: Supported by a frailty-focused communication educational aid, semi-structured interviews were conducted with 20 older adults residing in income-assisted housing. Follow-up interviews were conducted 2 weeks later. Descriptive content analysis was performed.Results: Participants mean age was 62.4, and 75% were African American. Six categories emerged to create a narrative of lower SES older adults' experiences, including (1) readiness to plan for aging and EOL, (2) interaction with the healthcare system, (3) daily life with insufficient resources, (4) the role of religiosity, (5) relationships with others, and (6) motivation and health status.Discussion: Life course vulnerabilities and struggles of lower SES older adults preclude opportunities to proactively plan for aging and EOL. Holistic interventions and innovative approaches are needed to address aging across the life course.